Hemoglobin A1c Level is Associated with Lymphovascular Space Invasion in Diabetic Endometrial Cancer Patients - Senkaya, Ayse Rabia; Kantarci, Sercan; Yildirim Karaca, Suna; Sanci, Muzaffer (Gynecology Obstetrics & Reproductive Medicine, 2024)
Objective: Our aim in this study is to examine the relationship of hemoglobin A1c (HbA1c) and fasting glucose with the stage, grade and histological type of cancer and its value in predicting the prognosis of endometrial cancer in diabetic endometrial cancer patients. Study Design: The data of 138 endometrial cancer patients with diabetes who met the study criteria were analyzed. Hemoglobin A1c levels and fasting glucose were compared with cancer stage, grade, histological type, lymphovascular invasion, chemotherapy and radiotherapy data. Results: A statistically significant difference was found between the groups in terms of HbA1c values only according to the lymphovascular invasion (p=0.02). While there was no significant correlation between endometrial thickness and HbA1c, a low positive correlation was found between the fasting glucose value (r=0.191, p=0.025) Conclusions: The higher rate of lymphovascular invasion in patients with high HbA1c value alone is insufficient in determining the prognosis when other parameters are considered.